Interbacterial Chemical Communication‐Triggered Nascent Proteomics. Issue 5 (19th December 2022) - Liu, Weibing; Tang, Qi; Meng, Liying; Hu, Shufan; Sun, De‐en; Li, Shan; Dai, Peng; Chen, Xing
Abstract: Metabolic labeling with clickable noncanonical amino acids has enabled nascent proteome profiling, which can be performed in a cell‐type‐specific manner. However, nascent proteomics in an intercellular communication‐dependent manner remains challenging. Here we develop communication‐activated profiling of protein expression (CAPPEX), which integrates the LuxI/LuxR quorum sensing circuit with the cell‐type‐specific nascent proteomics method to enable selective click‐labeling of newly synthesized proteins in a specific bacterium upon receiving chemical signals from another reporter bacterium. CAPPEX reveals that E. coli competes with Salmonella for tryptophan as the precursor for indole, and the resulting indole suppressed the expression of virulence factors in Salmonella . This tryptophan‐indole axis confers attenuation of Salmonella invasion in host cells and living mice. The CAPPEX strategy should be widely applicable for investigating various interbacterial communication processes. Abstract : The CAPPEX strategy enables communication‐triggered nascent proteomic analysis in complex bacterial populations. Applying CAPPEX, a tryptophan‐indole axis that contributes to the colonization resistance of commensal E. coli to Salmonella was discovered.